FRAILTY IN ELDERLY PEOPLE: INCIDENCE IN LONG-STAY FACILITY FOR ELDERLY PEOPLE IN SOUSA, PARAÍBA, BRAZIL (Fiep Bulletin - online, 2014)
Objective: Identify the incidence of frailty in elderly people in long-stay facility for elderly people (LFEP), using the phenotype proposed by Linda Fried and colleagues. Methodology: Exploratory study, with a quantitative approach, carried out in 2 LFEPs in the town of Sousa, Paraíba, Brazil. Data were collected in March 2013, using an instrument validated by Linda Fried and colleagues, with 25 elderly people, who made up the sample. Data were processed, stored, and analyzed using the software SPSS, version 20, after approval by the Research Ethics Committee of Faculdade Santa Maria, under the Protocol 216,953. Results: 17 elderly people (68%) were aged between 80 and 100 years and 20 (80%) were classified as frail. Among the other markers under analysis, smokers stood out, 13 elderly people (52%), and the former smokers, 12 (47%), who were classified as frail. Conclusions: Given the heterogeneous manifestation of pre-frailty and the clinical similarity between the groups non-frail and pre-frail, factorial analysis allowed confirming the main frailty markers. However, there is a need for investigating the frailty syndrome over time, analyzing how it is influenced and how it influences on individual's health perception. Keywords: Demographic aging. Elderly person. Fried's phenotype.  Long-stay facility for elderly people.